A Theoretical Analysis of Geopolitical Perspectives on Identity Crisis in Taslima Nasrin’s Lajja - T, RESHIKA.; P, Dr. REVATHI.; P, Dr. BINDHU; S, Dr. THAHERA. (Journal of Ecohumanism, 2024)
The focal point of this article is to critically analyze Taslima Nasrin’s Lajja (Shame, 1993) and to focus on the significant impact of geopolitics and religious fundamentalism on society to address the question of identity in the context of religion and nationality. The novel portrays the socio-cultural problems that emerged from the massacre of the masjid Babri and the consequent attacks on Hindus in Bangladesh. The Datta family experiences racial displacement amid rising waves of religious terrorism targeting minority Hindus. The paper examines how their sense of self is tested and transformed in the face of these events. This paper thoroughly examines Lajja, focusing on the impact of religious prejudice and its consequences in the social and political sphere through Geopolitical theory. It also offers a significant analysis of how religious extremists can exploit religion to create divisions within societies and marginalize certain. The novel’s narrative makes it timeless and relevant, highlighting the significance of fostering harmony and understanding among diverse beliefs within communities, particularly about the divisions caused by religious and philosophical conflicts. This contributes significantly to the context of religious acceptance in contemporary literature. The paper examines how their sense of self is tested and transformed in the face of these events, focusing on the impact of religious prejudice and its consequences in the social and political sphere. It also offers a significant analysis of how religious extremists can exploit religion to create divisions within societies and marginalize certain.